Effect of ploidy level on accumulation and depuration of Vibrio parahaemolyticus in Pacific oyster Crassostrea gigas - Sorée, Marion; Meleder, Anna Le; Maurouard, Elise; Lozach, Solen; Papin, Mathias; Stavrakakis, Christophe; Audemard, Corinne; Heath, Dominique Hervio; Dégremont, Lionel (Aquaculture, 2023)
Triploid cupped oysters represent an advantage over diploid oysters due to their faster growth and their whole year marketable span, especially during the spawning season occurring in the summer. Thus, their commer-cialization during this warm season could present a risk for human health due to the proliferation of human -pathogenic Vibrio spp. such as Vibrio parahaemolyticus (Vp). The purpose of this study was to evaluate the impact of Crassostrea gigas oyster ploidy on contamination with indigenous Vp in an oyster farm, and on the accumulation and depuration of Vp in laboratory experiments. The study was conducted from May through November 2021 using three batches of diploid oysters and three batches of triploid oysters. We observed that ploidy did not significantly influence contamination by indigenous Vp although the contamination with indig-enous Vp trended to be lower in triploids (0.93 log MPN.g(-1)) in comparison with diploids (3.08 log MPN.g(-1)) in November. These results could suggest a safer consumption of triploid oysters over diploid oysters in autumn concerning Vp infection risk in the site of this study. Moreover, pathogenic profiles of indigenous Vp varied significantly between July (8% of tdh(+) and 100 of trh(2+)) and November (98% of tdh(+) and 0% of trh(2+)) with no significant difference between ploidies. Ploidy did not significantly influence experimental accumulation or depuration at any time. However, depuration was higher during summer (June to August) than during the other months. In conclusion, our study suggests that Vp levels in C. gigas are not influenced by oyster ploidy. In addition, seasonal variations of indigenous Vp pathogenic profiles and Vp experimental depuration were observed.